Evaluation of Breast Cancer Awareness Among Female Students at Omdurman Islamic University (literary Faculties) - Hamed, Asrar Alnaim (2015)
Introduction: Breast cancer is the most frequent malignancy of women worldwide. Breast cancer is the most commonly diagnosed cancer in women and the second leading cause of death in women in Africa. In sudan no studies have been conducted to address breast cancer awareness . Objectives: The aim of this current study was therefore to evaluate the breast cancer awareness among female students at Omdurman Islamic University (literary colleges) focusing on knowledge of breast cancer signs and symptoms, risk factors, and breast self-examination (BSE). Methodology: The design of this study was an A cross sectional survey. The sample size was chosen randomly from the literary colleges ( 200 literary students). Data were collected using face-to-face interviews. The collected data was analyzed using spss. Results: Findings of this study show that students from literary students had moderate knowledge about symptoms of breast cancer and they had low knowledge about risk factors and BSE. so level of awareness of breast cancer is inadequate. Conclusion: Findings indicate that students level of awareness of breast cancer (i.e. knowledge of breast cancer signs and symptoms ) was adequate .On other hand level of awareness of breast cancer , (i.e. knowledge of risk factors, and breast self-examination (BSE) ) was low. Recommendation: Public awareness interventions are needed in order to overcome an ever-increasing burden of this disease. Women who are at high risk for breast cancer based on certain factors should get an MRI and a mammogram every year. Primary health care workers should be involved in such education program and they should be encouraged to participate in health education by provide information on breast cancer to their patients.